Management - Stoner, James Arthur Finch; Freeman, R. Edward (Englwood Cliffs, N.J. : Prentice Hall, 1989)
This deals with the entire management and its strategies. The book is divided into six parts namely: Introduction to management; planning and decision making; organising for stability and change; leading; controlling; and emerging concepts in management.
Includes bibliographical references and indexes.
MF23/01/2019
Loans
Keywords: Management; Administration